Overview of Cancer Control in Armenia and Policy Implications - Bedirian, Karen; Aghabekyan, Tigran; Mesrobian, Arianna; Shekherdimian, Shant; Zohrabyan, Davit; Safaryan, Liana; Sargsyan, Lilit; Avagyan, Armen; Harutyunyan, Lilit; Voskanyan, Astghik; Tadevosyan, Artashes; Melik-Nubaryan, Davit; et al. (Frontiers in Oncology, 2022)
Cancer is the second leading cause of death in Armenia. Over the past two decades, the country has seen a significant rise in cancer morbidity and mortality. This review aims to provide up-to-date info about the state of cancer control in Armenia and identify priority areas of research. The paper analyzes published literature and local and international statistical reports on Armenia and similar countries to put numbers into context. While cancer detection, diagnosis, and treatment are improving, the prevalence of risk factors is still quite high and smoking is widespread. Early detection rates are low and several important screening programs are absent. Diagnosis and treatment methods are not standardized; there is a lack of treatment accessibility due to insufficient government coverage and limited availability of essential medicines. Overall, there is room for improvement in this sector, as research is limited and multidisciplinary approaches to the topic are rare.